Heo started to solve the quadratic equation (x + 2)2 – 9 = –5. He added 9 to both sides and the resulting equation was (x + 2)2
= 4. Next, he took the square root of each side. Which was the resulting equation of that step?
1 answer:
Step-by-step explanation:
After taking the square root:
x + 2 = ±2
Notice that x + 2 can also equal -2, because (-2)² = 4.
You might be interested in
Rational because you get a whole number
You need to post an actual question on her to be answered
4 and 6!
4*6 = 24
24 - 14 = 10
4 + 6 = 10